2017
DOI: 10.1590/0001-3765201720160111
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate solubilization by endophytic bacteria isolated from banana trees

Abstract: Forty isolates of endophytic bacteria isolated from banana tree roots were assessed as to their capacity to solubilize phosphate in a solid culture medium supplemented with different inorganic and one organic source of phosphorus. The amount of phosphorus (P) in each liquid medium was quantified, and an indirect assessment of acid phosphatase activity was performed. All assays had a fully randomized design, with three repetitions. Approximately 67.5% of the 40 isolates assessed in solid medium solubilized phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 26 publications
1
28
0
8
Order By: Relevance
“…TNC-1, the highest amount of soluble P was associated with a decrease in the pH to 4.93. These data indicate that the solubilization process of P is consistent with the bacterial excretion of substances that acidified the culture broth [61]. Several reports indicate that organic acid (OA) and siderophores production are among the mechanisms underlying inorganic P solubilization [62,63].…”
Section: Pgp Potentials Of Extremophilic Actinobacteriasupporting
confidence: 65%
“…TNC-1, the highest amount of soluble P was associated with a decrease in the pH to 4.93. These data indicate that the solubilization process of P is consistent with the bacterial excretion of substances that acidified the culture broth [61]. Several reports indicate that organic acid (OA) and siderophores production are among the mechanisms underlying inorganic P solubilization [62,63].…”
Section: Pgp Potentials Of Extremophilic Actinobacteriasupporting
confidence: 65%
“…Additionally, Phosphorus is essential element for plants growth and development, but its present in agriculture soils in low amount [44,45]. Endophytes are known to improve plant growth by the phosphate solubilization [46,47]. In the study conducted by Ullah et al [43] all tested endophytic bacterial strains were found to have the potential to solubilize phosphorous.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a greater potential for solubilization of AP by endophytic bacteria compared to rhizosphere bacteria ( Figure 1A, p < 0.05). This effect of the origin site of bacteria of maize microbiome on P solubilization still needs to be further investigated, since numerous studies report this potential for bacteria isolated both from internal maize tissues (Matos et al, 2017;de Sousa et al, 2020) and the plant rhizosphere (Gomes et al, 2014;Li et al, 2017). It was expected that this greater potential was more related to rhizospheric bacteria that live in soil containing P insoluble forms.…”
Section: Enrichment Of Bacterial Taxa From Soil Rhizospheric Cultivatmentioning
confidence: 99%